2002
DOI: 10.1097/00000542-200202000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Trial Design for Eliciting a Pharmacokinetic– Pharmacodynamic Model–based Response Surface Describing the Interaction between Two Intravenous Anesthetic Drugs

Abstract: The results showed that a number of trial designs would be viable, but a design that crossed the surface in a crisscross fashion would give the most robust result with the least patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…When more than one drug is administered to produce an anesthetic effect, as in clinical practice, multiple sigmoid curves can be generated for each concentration of a particular drug. 15,16 Propofol and remifentanil were infused together to produce the measured anesthetic endpoint, which is "response" or "no response" to the stimulus of the procedure. Several pharmacodynamic models were considered to first determine whether there was a significant interaction between the two drugs; subsequently, models were considered that would best characterize the interaction between the two drugs.…”
Section: Deriving the Interaction From The Study Datamentioning
confidence: 99%
“…When more than one drug is administered to produce an anesthetic effect, as in clinical practice, multiple sigmoid curves can be generated for each concentration of a particular drug. 15,16 Propofol and remifentanil were infused together to produce the measured anesthetic endpoint, which is "response" or "no response" to the stimulus of the procedure. Several pharmacodynamic models were considered to first determine whether there was a significant interaction between the two drugs; subsequently, models were considered that would best characterize the interaction between the two drugs.…”
Section: Deriving the Interaction From The Study Datamentioning
confidence: 99%
“…The study was originally designed and powered to develop a propofol-remifentanil pharmacodynamic model and 24 volunteers were chosen because Short et al 15 had shown that 20 subjects would be required to define a model surface adequately using a crisscross study design for assessing drug interaction. The ethics approval was to collect the original volunteer data.…”
Section: Volunteer Recruitment and Instrumentationmentioning
confidence: 99%
“…Dosing Regimen. The study design was a modification of the criss-cross design proposed by Short et al 3 The choice of the sevoflurane/remifentanil concentrations pairs were based on the sevoflurane Ce50 (Ce50 sevo ) to suppress the response to skin incision (ϭ minimal anesthetic concentration, MAC) of 1.85% 13 and a remifentanil Ce50 (ϭ remifentanil concentration reducing the MAC SEVO by 50%) of 1.5 ng/ml 14 :…”
Section: Drug Administrationmentioning
confidence: 99%
“…1,2 Using the mathematically defined response surface, the corresponding drug effect for any two or more drug concentrations of the interacting drugs can be predicted. 1,3 Various methodological approaches to response surface models are found in the literature. Bol et al further developed a previously published response surface model by Greco et al to describe the interaction between dexmedetomidine and midazolam in rats.…”
mentioning
confidence: 99%